The power of engagement : a selection of inspiring community engaged initiatives (Penerbit Universiti Kebangsaan Malaysia, 2012)
"Community engagement has always been a strong feature and a key strategy at Universiti Kebangsaan Malaysia (The National University of Malaysia, UKM). This publication showcases a compilation of stories on exemplary community engagement initiatives at UKM. To provide the context for areas pertinent to community engagement, the selection includes innovative projects which cut across a broad range of issues such as health, education, environment, social enterprise, youth and under-served communities as well as volunteerism. By focusing on success stories that can impart a better understanding of the modality, challenges and rewards of implementing collaborative community engagement initiatives with multi-stakeholders, this publication aims to inspire like-minded individuals and institutions towards forging meaningful links with their respective communities. It is hope that the selection of stories featured here can enhance awareness of the mutual benefits of community engagement across research, education and service, and ultimately contribute towards developing vibrant and dynamic engagement initiatives for regional community development"--